Akad Wadi’ah Dalam Perspektif Ulama Madzhab - Saepudin, Saep; Syaripudin, Enceng Iip; Nuraeni, Neni; Januri, Fauzan (Jurnal Hukum Ekonomi Syariah, 2022)
In Fiqh Muamalah, there is one contract performed in an effort to safeguard someone's wealth, namely the wadhiah contract, because through this contract, each individual inherently possesses varying abilities, including in safeguarding their wealth. The wadhiah contract is not a new concept; there have been numerous writings discussing wadhiah. In this particular text, the author will specifically delve into the wadhiah contract from the perspective of Fiqh Muamalah. Therefore, the author will attempt to examine this entrusted property from the viewpoints of scholars from different schools of thought who have differing interpretations/definitions of wadhiah.   From a jurisprudential standpoint, wadhiah is understood as a pure trust without any risk based on the contract of tabarru (mutual assistance); where the parties agree that there is no profit or benefit motivating their actions. The Hanafi scholars define wadhiah as involving others in the preservation of wealth, either explicitly or implicitly. As for the majority of scholars (Maliki, Shafi'i, Hanbali), wadhiah is defined as entrusting someone else to safeguard certain assets in a specific manner.  Keywords: wadhiah, Scholars, Perspective, Schools of Thought.